The Thiopurine Tale: An Unexpected Journey. (12th January 2022) - Crouwel, Femke; Buiter, Hans J C; de Boer, Nanne K
Abstract: Exactly 70 years ago [1951] mercaptopurine was discovered by Gertrude Elion as a novel treatment option for acute leukaemia. A total of three thiopurines (also thioguanine [1950] and azathioprine [1957]) were developed over time. These immunosuppressive drugs were also successfully introduced a few decades later to prevent rejection of transplanted organs and to treat several autoimmune diseases. For her discovery of thiopurines and other antimetabolite drugs, in 1988 Elion was rewarded, together with George Hitchings and James Black, with the Nobel Prize in Physiology or Medicine. Important steps have been made in recent years to unravel its metabolism, mode of action and pharmacogenetics. Today thiopurine [based] therapy remains an essential immunosuppressive approach in treating patients with inflammatory bowel disease.